Factors that contribute to the immmunogenicity of therapeutic recombinant human proteins - Mukovozov, Ilya; Sabljic, Thomas; Hortelano, Gonzalo; Ofosu, Frederick A (Thrombosis and haemostasis, 2008)
Use of recombinant human proteins has revolutionized medicine by providing over 200 highly purified hormones and proteins that effectively treat many inherited and acquired peptide hormone and protein deficiencies. With the exception of therapeutic monoclonal antibodies, these biological medicines are synthesized by cultured cells using DNA sequences that would yield proteins with identical amino acid sequences as endogenous human proteins. Therefore, there was the broad expectation that recombinant human biological medicines would be non-immunogenic in patients capable of synthesizing even sub-optimal levels of these therapeutic proteins to which they are innately tolerant. However, the widespread clinical use of recombinant human proteins has demonstrated that nearly all of them are immunogenic. This observation suggests that factors additional to differences in amino acid sequences of endogenous and biotherapeutic proteins contribute to the immunogenicity of therapeutic proteins. The main aim of this review is to summarize some of the factors that are known to contribute to the immunogenicity of recombinant therapeutic proteins.